The Paired-Domain Transcription Factor Pax8 Binds to the Upstream Enhancer of the Rat Sodium/Iodide Symporter Gene and Participates in Both Thyroid-Specific and Cyclic-AMP-Dependent Transcription - Ohno, Makoto (American Society for Microbiology, 1999)
The gene encoding the Na/I symporter (NIS) is expressed at high levels only in thyroid follicular cells, where its expression is regulated by the thyroid-stimulating hormone via the second messenger, cyclic AMP (cAMP). In this study, we demonstrate the presence of an enhancer that is located between nucleotides −2264 and −2495 in the 5′-flanking region of the NIS gene and that recapitulates the most relevant aspects of NIS regulation. When fused to either its own or a heterologous promoter, the NIS upstream enhancer, which we call NUE, stimulates transcription in a thyroid-specific and cAMP-dependent manner. The activity of NUE depends on the four most relevant sites, identified by mutational analysis. The thyroid-specific transcription factor Pax8 binds at two of these sites. Mutations that interfere with Pax8 binding also decrease transcriptional activity of the NUE. Furthermore, expression of Pax8 in nonthyroid cells results in transcriptional activation of NUE, strongly suggesting that the paired-domain protein Pax8 plays an important role in NUE activity. The NUE responds to cAMP in both protein kinase A-dependent and -independent manners, indicating that this enhancer could represent a novel type of cAMP responsive element. Such a cAMP response requires Pax8 but also depends on the integrity of a cAMP responsive element (CRE)-like sequence, thus suggesting a functional interaction between Pax8 and factors binding at the CRE-like site.